Pattern Of Dermatosis In Geriaritic Patients Attending A Secondary Health Care Centre In A Rural Area (Journal of Pharmaceutical Negative Results, 2023)
Background: Improving healthcare facilities and socioeconomic parameters, have increased the life expectancy, and thus the size of geriaritic population. Geriaritic dermatosis along with other geriaritic diseases, are also more prevalent.Aims and objectives: To determine the pattern of dermatosis in geriaritic subgroup of our populationMaterial and methods: This study involving 300 patients over 60 years of age, was conducted in the outpatient department (OPD) of dermatology of a secondary care centre. A detailed history and examination of cutaneous and systemic complaints was done. Diagnosis was done on clinical assessment, and investigations were done whenever required. All the findings were recorded and analysed .Results: Out of the total of 300 patients, 176 were males as compared to 124 females (1.41:1). Mean age was 66.92 + 6.31years, with majority belonging to under 70years of age (62.66%). Most common dermatosis were infections followed by eczemas. Commonest presenting symptom was pruritus (68.33%). Systemic complaints were present in 166(55.33%) patients, hypertension (26.33%) being the commonest.Conclusion: Proper management of these geriaritic dermatosis requires enhanced awareness and knowledge about their pattern and prevalence.